The Welfare Cost of Lawlessness: Evidence from Somali Piracy. Issue 2 (1st April 2015) - Besley, Timothy; Fetzer, Thiemo; Mueller, Hannes
Abstract: In spite of general agreement that establishing the rule of law is central to properly functioning economies, little is known about the cost of law and order breakdowns. This paper studies a specific context of this by estimating the effect of Somali piracy attacks on shipping costs using data on shipping contracts in the dry bulk market. To estimate the effect of piracy, we look at shipping routes whose shortest path exposes them to piracy and find that the increase in attacks in 2008 led to around an 8% to 12% increase in costs. From this we calculate the welfare loss imposed by piracy. We estimate that generating around 120 USD million of revenue for Somali pirates led to a welfare loss in excess of 630 USD million, making piracy an expensive way of making transfers.